Efficacy of using 810-nm diode laser after impacted lower third molar extraction surgery at Hue University of Medicine and Pharmacy Hospital - Dang, Minh Huy; Cung, Thien Hai; Le, Thi Nhat Linh; Nguyen, Van Minh; Tran, Tan Tai (Tạp chí Y Dược Huế, 2024)
Backgroud: Third molar extraction surgery often has many postoperative complications and the most common of them are pain, swelling and trismus. Currently, researchers pay attention and apply 810-nm diode laser in treatment to help patients return to normal daily life quickly. Objectives: This study aimed to investigate the effectiveness of 810-nm diode laser after impacted lower third molar extraction surgery. Materials and Methods: 60 patients, who underwent impacted lower third molar extraction surgery at Dental Clinic, Hue University of Medicine and Pharmacy Hospital, were divided randomly into 2 groups. In Diode laser group, each patient is applied 810-nm diode laser, power 0,5W at 6 points (22 seconds per point) with total energy 66J and power density 27.5 J/cm2 after surgery. In control group, the same procedures were set up at surgical site but diode laser was not activated. Patients were evaluated for the intensity of the pain by VAS score during 7 days and the number of painkiller during 2 days after surgery. All the patients were assessed for swelling and trismus at postoperative intervals of 1, 2 and 7 days. Results: The number of painkiller used in Diode laser group in first 2 days after lower third molar extraction surgery was 1.20 ± 0.50 tablets, while the control group was 2.50 ± 0.57 tablets. The pain intensity of Diode laser group is lower than that of control group in first 6 days after surgery significantly (p < 0.05). The facial swelling and trismus of Diode laser group is lower than that of control group at day 1 and day 2 after surgery significantly (p<0.05). Conclusion: 810-nm diode laser therapy effectively reduces pain, swelling and trismus after impacted lower third molar extraction surgery.